2020
DOI: 10.1038/s41593-019-0578-x
|View full text |Cite
|
Sign up to set email alerts
|

A myelin-related transcriptomic profile is shared by Pitt–Hopkins syndrome models and human autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is genetically heterogeneous with convergent symptomatology, suggesting common dysregulated pathways. We analyzed brain transcriptional changes in five mouse models of Pitt-Hopkins Syndrome (PTHS), a syndromic form of ASD caused by mutations in TCF4 (transcription factor 4, not TCF7L2 / T-Cell Factor 4). Analyses of differentially expressed genes (DEGs) highlighted oligodendrocyte (OL) dysregulation, which we confirmed in two addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
135
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(147 citation statements)
references
References 71 publications
12
135
0
Order By: Relevance
“…Thus, these data suggest that the deletion of Zbtb16 results in abnormal oligodendrogenesis, and eventually causes behavioral abnormalities such as ASD-and SCZ-like phenotypes. A recent study examined the role of the ASD-relevant gene TCF4 and found that Tcf4 mutant mice show impairments of oligodendrocyte development and myelination, supporting the significance of oligodendrocytes implicating ASD etiology 75 . In addition, reductions in white matter or corpus callosum volumes in the brains of ASD 76,77 and SCZ 78,79 subjects using diffusion tensor imaging (DTI) have been reported.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, these data suggest that the deletion of Zbtb16 results in abnormal oligodendrogenesis, and eventually causes behavioral abnormalities such as ASD-and SCZ-like phenotypes. A recent study examined the role of the ASD-relevant gene TCF4 and found that Tcf4 mutant mice show impairments of oligodendrocyte development and myelination, supporting the significance of oligodendrocytes implicating ASD etiology 75 . In addition, reductions in white matter or corpus callosum volumes in the brains of ASD 76,77 and SCZ 78,79 subjects using diffusion tensor imaging (DTI) have been reported.…”
Section: Discussionmentioning
confidence: 92%
“…Given our primary goal to gain rst insight how Tcf4 haploinsu ciency, which has been causally linked to neurodevelopmental disorders such as Pitt-Hopkins Syndrome and intellectual disability, affects adult neurogenesis, we analysed constitutive heterozygote Tcf4 knockout mice. TCF4 expression is broadly expressed and is critical for the development of a number of neural and non-neural cell types (18,(45)(46)(47)(48). It therefore remains to be determined how decreased TCF4 dosage in different cell populations contribute to the impairment in adult hippocampal neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Given our primary goal to gain rst insight how Tcf4 haploinsu ciency, which has been causally linked to neurodevelopmental disorders such as Pitt-Hopkins Syndrome and intellectual disability, affects adult neurogenesis, we analysed constitutive heterozygote Tcf4 knockout mice. TCF4 is broadly expressed and is critical for the development of a number of neural and non-neural cell types (18,(45)(46)(47)(48). It therefore remains to be determined how decreased TCF4 dosage in different cell populations contributes to the impairment in adult hippocampal neurogenesis.…”
Section: Discussionmentioning
confidence: 99%